Intelligence and intelligence testing - Fletcher, Richard B.; Hattie, John. (London : Routledge, 2011)
Praise for Visible Learning by John Hattie' The Holy Grail of Educational research' -Times Educational Supplement'Visible Learning is the definitive book on sorting out the effectiveness of teaching strategies - a must read for those who want to improve teaching and learning.' - Michael Fullan Have you ever wondered what IQ is and how it is measured? Indeed, why is there such a premium placed on high IQ? What do we mean by intelligence? What is your IQ? What does your IQ score mean? There can be no denying the enduring appeal of IQ over....
Keywords: Intelligence levels; Intelligence tests -- History